2020
DOI: 10.2147/ijn.s251760
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ag/Au Bimetallic Nanoparticles Inhibit Tumor Growth and Prevent Metastasis in a Mouse Model</p>

Abstract: Purpose: To evaluate the antitumor efficacy of Ag 3 Au 1 Trp 1:2 NPs in a SCID mouse cancer model, with respect to their effect on tumor growth, on tumor's metastatic potential and the underlying molecular mechanism. Subjects and Methods: Ag 3 Au 1 Trp 1:2 NPs were radiolabeled with Gallium-68 and the biodistribution was studied in Swiss mice without tumors and in SCID mice bearing tumors. SCID mice received intratumoral Ag 3 Au 1 Trp 1:2 NPs and tumor size was measured using calipers. Lung and liver tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“… Poor radiation tolerance. Ag/Au bimetallic nanoparticles [168] NOD-SCID Lacks mature B and T cells. Reduced innate immunity.…”
Section: Pre-clinical Breast Cancer Animal Modelsmentioning
confidence: 99%
“… Poor radiation tolerance. Ag/Au bimetallic nanoparticles [168] NOD-SCID Lacks mature B and T cells. Reduced innate immunity.…”
Section: Pre-clinical Breast Cancer Animal Modelsmentioning
confidence: 99%
“…In vivo, NPs need to overcome many physiological barriers, including clearance by immune cells in the liver and spleen, various endothelial membranes, interstitial spaces, the plasma membrane, endosomal/lysosomal membranes and finally the nuclear membrane and pore complex [ 203 ]. Upon intravenous injection, a fraction of NPs reaches the TME primarily via the EPR effect, while another part is taken up by the macrophages of the liver and spleen, which are in direct contact with the bloodstream [ 204 , 205 ]. In addition, the abnormal structure of blood vessels in tumors allows the penetration of NPs, while defects in the lymphatic system facilitate the retention of NPs in the TME, where they slowly release their payload, such as antitumor drugs [ 206 , 207 ].…”
Section: Interaction Of Macrophages With Npsmentioning
confidence: 99%
“…Here we can state that Au based bimetallic NPs show better cytotoxic properties due to their excellent optical features and biochemical consistency thereby enhancing the properties as bimetallic NPs. Katifelis et al 92 reported that bimetallic Au–Ag alloy synthesized via chemical reduction activated caspase cascade in mice with tumor.…”
Section: Resultsmentioning
confidence: 99%
“…10 nm) are said to coat plasma membrane prior to their incorporation whereas larger NPs (100 nm) are directly internalized without accumulating onto cell membrane. 92 The major endocytosis mechanisms for NPs uptake are phagocytosis, diffusion, pinocytosis and clathrin/caveolae-mediated endocytosis. 97 Factors such as NPs size, morphology, surface chemistry and incubation environment affect the uptake and internalization of NPs.…”
Section: Resultsmentioning
confidence: 99%